Pemodelan Dan Simulasi Battery Charger Berbasis Push-Pull Converter Menggunakan Matlab-Simulink - Anto, Budhi; Padang, Muhammad Ulfy Syafe’i (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Battery is an alternative energy source and it is important for energy storage. Battery is often used as energy reserves but the energy in the battery is not able to maintain for longer time. Therefore the battery need to be recharged. This paper proposed a push-pull converter design which is supplied by PLN. In the push-pull converter design the output voltage is constantly in 14.1 volt value with the current of 2.16 ampere. The battery type that being used is sealed lead acid (SLA) which has a capacityof 7.2 Ah with a nominal voltage of 12 volt. The system was designed using MATLAB-Simulink software. The result of simulation shows in three scenarios in example the output of converter when the input fluctuation condition, the load of converter when the input steady state condition, then it connect to battery for charging purpose output of converter already in stable condition.Keywords : Push-pull Converter, Sealed Lead Acid Battery, MATLAB-Simulink